Gestión financiera de la empresa Agroinsumos Karlita del cantón Ventanas periodo 2019-2020 - Soria Valle, Ruth Ana (2021)
The purpose of this project is to research and document the case study carried out at Agroinsumos Karlita, which has the objective of determining financial management and its impact on the profitability of the company. To obtain this information, the vertical and horizontal analysis of the most relevant income statements was applied, which are the statement of financial position and statement of comprehensive income for the periods 2019 - 2020. The appropriate financial ratios were also applied, which allowed to obtain the information necessary for the issuance of an adequate pronouncement. The hypothetical deductive method was applied with a descriptive research approach and non-experimental design. All the information obtained for the elaboration of this project was provided by the person in charge of the company, who provided us with the survey and all the necessary documentation for the adequate fulfillment of the process. The most relevant results of the investigation show that the company, although it has an acceptable level of liquidity, had a drop in 2019 of almost 0.40 in its liquidity. There were expense accounts that, although they were made in both periods, sent them to other expenses and are not reflected in the income statement as advertising. According to the interview, the dynamics of the process or treatment of accounting and financial information is described a little, the management of financial decisions is in charge of the manager and the accountant, they do not have a financial advisor who is explicitly in charge in this area. Since the creation of the company Agroinsumos Karlita, basic activities have been carried out, such as making declarations and preparing annual financial statements.